2018
DOI: 10.1186/s12916-018-1103-x
|View full text |Cite
|
Sign up to set email alerts
|

Real-world data reveal a diagnostic gap in non-alcoholic fatty liver disease

Abstract: BackgroundNon-alcoholic fatty liver disease (NAFLD) is the most common cause of liver disease worldwide. It affects an estimated 20% of the general population, based on cohort studies of varying size and heterogeneous selection. However, the prevalence and incidence of recorded NAFLD diagnoses in unselected real-world health-care records is unknown. We harmonised health records from four major European territories and assessed age- and sex-specific point prevalence and incidence of NAFLD over the past decade.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
175
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 209 publications
(198 citation statements)
references
References 41 publications
5
175
0
1
Order By: Relevance
“…In addition, alcohol intake may interact with genetic variants that predispose to liver injury. For instance, PNPLA3 148M homozygosity conferred significant additional mortality risk in patients with severe alcoholic hepatitis . Similar to our previous studies, we did not exclude persons based on reported alcohol use; instead, we adjusted for alcohol intake in multivariate analyses to present a more comprehensive picture of the FLD epidemic …”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In addition, alcohol intake may interact with genetic variants that predispose to liver injury. For instance, PNPLA3 148M homozygosity conferred significant additional mortality risk in patients with severe alcoholic hepatitis . Similar to our previous studies, we did not exclude persons based on reported alcohol use; instead, we adjusted for alcohol intake in multivariate analyses to present a more comprehensive picture of the FLD epidemic …”
Section: Discussionmentioning
confidence: 94%
“…In another report, 148M homozygosity doubled the risk of hepatic decompensation and liver disease mortality in patients with FLD‐associated portal hypertension . In patients with severe alcoholic hepatitis, 148M homozygosity conferred a 70% higher mortality risk …”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…For this reason it is often underdiagnosed. 9 If identified at its early stages and appropriate intervention initiated, NAFLD, NASH and fibrosis can be reversible. Independent risk factors for a recorded diagnosis of NAFLD include male sex, diabetes, hypertension and rising BMI category.…”
Section: Diagnosis In a Non-specialist Settingmentioning
confidence: 99%